Ensino de diagnóstico de enfermagem : uma estratégia educativa fundamentada na aprendizagem baseada em problemas - Lira, Ana Luisa Brandão de Carvalho (2009)
The teaching of nursing diagnoses enables to the student the accomplishment of the clinical evaluation, the direction of their actions according to the needs to client and the deepening of your knowledge on the professional practice, providing basic support to deliver care. However, there is, in practice, some difficulty in consolidating the teaching of such diagnoses. The development of educational strategies that give students an active stance, critical and creative, is necessary. This study aimed to evaluate the effectiveness of a teaching strategy about nursing diagnoses based on Problem Based Learning (PBL) in the performance of nursing students´ clinical reasoning and diagnosis trial. And as specific: to check the validity of the content of the problems in the application of educational strategy, and raise the scores of students in identifying the defining characteristics, nursing diagnoses and related or risk factors before and after the development of educational strategy. It was an experimental study, organized in two phases. In the first, five specialists validated the contents of four problems, during June and July months 2009. The problems addressed situations involving an adolescent with asthma, one woman underwent a cholecystectomy, a man with sequelae of a stroke, together at home, and a client with hypertension was referred to the clinic for treatment of the family. The data collection instruments were a script to evaluate the item-objective congruence and a script to identify the defining characteristics, diagnoses and related factors or risk. The second phase of the study was the application of educational strategy. Participated in this phase, 30 students enrolled in a federal university located in the region of Trairi of Rio Grande do Norte, chosen for convenience. Inclusion criteria were: being a graduate student in nursing, has completed the approval Semiology and Semiotechnique at this university for the semester 2009.1, and consent to participate in all phases of research. The exclusion criteria was: not being able to participate in all phases of research. The students were distributed of aleatory form in two groups, 15 in experimental and 15 in the control. The experimental group participated in the educational strategy, during August month 2009. The educational strategy was organized in the course form, with five modules, each involving a different problem, as recommended by the PBL. The study was approved by the Committee for Ethics and Research. The results showed that of the four problems developed in the first phase, just both first reached Content Validity Index (CVI) of 90%. The third and fourth problems were changed and re-evaluated by the specialists, receiving CVI average of 90% and 95% respectively. These problems were discussed during the five modules of the course held in the second phase of the study. The course effectiveness evaluation was measure by the application of a pre and one post-test. In the pre-test, both groups identified the characteristics, the diagnoses and the related factors of homogeneous form. In the post-test, the students of the experimental group identified a larger number of nursing diagnoses and related or risk factors. Besides the identification of few defining characteristics in the post-test both of by the groups, it can complete that there was influence of the implement strategy, because the results showed improvement in the data grouping capacity of the students of the experimental group. As noted, the PBL favored the performance of clinical reasoning and diagnosis of student trial undergraduate nursing